The practical management of Swimmer's painful shoulder: Etiology, diagnosis, and treatment - Bak, K. (Clinical Journal of Sport Medicine, 2010)
Shoulder pain is the most common musculoskeletal complaint in competitive swimmers. Problems with the shoulders of swimmers resemble that of the disabled thrower's shoulder, but the clinical findings and associated dysfunctions are not quite the same. Therefore, swimmers with shoulder pain should be evaluated and treated as a separate clinical entity, aimed toward underlying pathology and dysfunction. Balanced strength training of the rotator cuff, improvement of core stability, and correction of scapular dysfunction is central in treatment and prevention. Technical and training mistakes are still a major cause of shoulder pain, and intervention studies that focus on this are desirable. Imaging modalities rarely help clarify the diagnosis, their main role being exclusion of other pathology. If nonoperative treatment fails, an arthroscopy with debridement, repair, or reduction of capsular hyperlaxity is indicated. The return rate and performance after surgery is low, except in cases where minor glenohumeral instability is predominant. Overall, the evidence for clinical presentation and management of swimmer's shoulder pain is sparse. Preliminary results of an intervention study show that scapular dyskinesis can be prevented in some swimmers. This may lead to a reduction of swimmer's shoulder problems in the future.